analisis pengaruh kualitas pelayanan, fasilitas pelayanan dan biaya pelayanan terhadap tingkat kepuasan masyarakat kelurahan sawahan - Ekhwan Yogi Saputro; Maya Widyana Dewi; Wikan Budi Utami (Jurnal Akuntansi dan Pajak, 2021)
The purpose of this study was to determine the effect of service quality, service facilities, and service costs on the level of community satisfaction in the Sawahan Village. The methodology used in this research is the quantitative data analysis method and the test is done by using multiple regression models. The population used is all people who take care of important documents in 2020 in Sawahan Village. The sample boundaries are citizens who take care of important papers in September-November 2020. In this study, a sample of 68 people was obtained. Based on the test results it can be concluded that the value ofthe variable service Quality of 4.426 is greater than ttable 1.66864. With a significance value of 0.000 smaller than α = 0.05. means that Ho is rejected, this shows that the Service Quality variable has a significant effect on community satisfaction. The t-count value of the Service Facility variable was 3.697, which was greater than the t-table value of 1.66864. With a significant value of 0.000 greater than α = 0.05. This shows that the Service Facility variable has an effect on community satisfaction. The count value of the Service Cost variable is 1.472 smaller than the ttable 1.66864. With a significant value of 0.146 which is greater than α = 0.05. This shows that the Service Cost variable has no effect on community satisfaction. Based on the results of the data test, the Fcount of 66.347 is greater than the Ftable 2.75 with a significance of 0.000 smaller than the significant value α = 0.05 so it can be concluded that simultaneously or together the variables of Service Quality, Service Facilities, and Service Costs is a factor that affects the Community Satisfaction variable. Keywords: Service Quality, Service Facilities, Service Costs, Community Satisfaction